Pemetaan Distribusi Aparatur Sipil Negara (ASN) Berdasarkan Status Kepegawaian Dalam Mendukung Pelayanan Publik Di Nabire, Papua Tengah - Fauzia Fajriyati; Usman Arfan (Jurnal Teknologi dan Informatika, 2025)
This investigation endeavors to elucidate the spatial distribution of Civil Servants (ASN) in Nabire Regency, Central Papua, with a particular emphasis on their employment status and its implications for public service delivery. Underpinned by the pivotal role of ASN in governance and the provision of effective public services, this study seeks to address the challenges associated with the management of disparate spatial and non-spatial personnel data. Utilizing Geographic Information System (GIS) methodology, this research facilitates a nuanced analysis and visualization of ASN data, stratified by geographical location and employment status, including civil servants, government employees with work contracts, and contract workers. The findings underscore the significance of mapping ASN distribution in identifying regional disparities, particularly in remote and underdeveloped areas such as Nabire. Moreover, the efficacy of ArcMap software from the ArcGIS platform in generating precise ASN distribution maps is demonstrated, thereby informing evidence-based policy formulation. The study's implications highlight the necessity for a reassessment of ASN requirements to ensure the judicious and equitable appointment of government employees with work contracts and civil servants, ultimately enhancing public service provision.